Faktor-Faktor yang Mempengaruhi Pemahaman Petani tentang Zakat Pertanian dan Peran Lembaga Zakat Desa: Bukti dari Kabupaten Enrekang - Devi Damayanti; Rukiah; Hannani; Umaima (Department of Management Zakat and Waqf, 2025)
Agricultural zakat has considerable potential to support poverty alleviation and strengthen Islamic social finance. However, the realization of agricultural zakat collection remains relatively low due to the limited understanding of farmers regarding the legal basis, nisab, calculation methods, and distribution mechanisms of agricultural zakat. This study aims to analyze farmers' understanding of agricultural zakat and examine the strategies implemented by the Village Zakat Collection Unit (UPZ) to improve public awareness and compliance in paying agricultural zakat. This research employed a qualitative approach using a phenomenological design. Data were collected through observation, in-depth interviews, and documentation involving rice farmers, village officials, and UPZ administrators in Karrang Village, Cendana District, Enrekang Regency. The data were analyzed using data reduction, data display, and conclusion drawing, while data validity was ensured through source triangulation. The findings reveal that most farmers possess limited knowledge of agricultural zakat and generally associate zakat solely with zakat al-fitr. Their understanding of nisab, zakat rates, and payment procedures remains inadequate, resulting in low compliance with agricultural zakat obligations. The study also finds that the UPZ has implemented several educational strategies, including Ramadan outreach programs, religious gathering campaigns, and socialization during Islamic celebrations. Nevertheless, these efforts have not yet achieved optimal outcomes due to low community participation and insufficient continuity of educational activities. The study concludes that strengthening zakat literacy through continuous education, collaboration among religious institutions, local government, and community leaders, as well as improving the capacity of UPZ, are essential to enhance farmers' understanding and increase agricultural zakat compliance.